Media ecological orientations to philosophy and philosophical problems. Issue 4 (2nd October 2017) - Anton, Corey
ABSTRACT: This introduction to the Media Ecology special issue of the Review of Communication provides a broad overview of the history of media ecology, clarifies its main orientations and key thinkers, and then illustrates how problems and orientations within philosophy are symptoms of various kinds of technological mediation.